Validity and reliability properties of the Persian version of perceived health competence scale among patients with cardiovascular diseases - Elham Shakibazadeh; Maryam Sabouri; Bahram Mohebbi; Azar Tol; Mehdi Yaseri (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Cardiovascular diseases are among progressive diseases that begin in childhood and are manifested mainly in adulthood. This study was assessed the validity and reliability testing of the Persian version of the Perceived Health Competence Scale (PHCS) among patients with cardiovascular diseases referred to Shahid Rajaie Heart center in Tehran, Iran. METHODS: In this cross-sectional study, a convenience sample of 700 patients with cardiovascular diseases referring to Shahid Rajaie Heart center in Tehran were recruited (response rate = 100%; n = 700). Content validity was established using translation and back-translation procedure and getting views of the expert panel. The content validity of the questionnaire was measured using content validity ratio (CVR) and content validity index (CVI). Reliability was ascertained using Cronbach's alpha. The stability was confirmed using intra-class correlation coefficients. RESULTS: In this study, CVI = 0.81 and CVR = 0.72 were calculated. Scale reliability was sufficient (α = 0.78; range = 0.73-0.77). Furthermore, reliability based on the stability of the whole scale was 0.75. CONCLUSIONS: The PHCS-Persian confirmed as a valid and reliable instrument to measure perceived health competence. The PHCS-Persian scale could be a useful, comprehensive, and culturally sensitive scale for assessing perceived health competence.